The experience of scavengers Who Dropped Out of School in Formal Education - Yanti Sri Wahyuni (Jurnal Ilmu Sosial Mamangan, 2019)
Education is very important in life and it can support the future. Everyone has the right to education, both formal and informal, as well as scavenger children. Based on field data, we can see that many scavenger drop out of school because they cannot afford to pay for their children's education. Although there are some scavengers who go to school, only elementary and then do not continue to a higher level. The purpose of this study is to describe the experiences of scavengers who drop out of school at the level of formal education. The approach used in this study is a qualitative approach and the type of research is descriptive because to describe the data in the field, the informants in this study were scavengers and data croschecks conducted interviews with parents and the school. Data were collected by means of in-depth interviews with informants, and documentation, data were analyzed by means of an interactive model of Mathew Milles And Huberman. The results of this study Some of the scavenging children had unfavorable experiences when they were on school benches and there were also some scavenging children who had a pleasant experience for them. Experiences that are felt to be not good for scavengers like when they are in school they get actions ostracized.